Acute renal failure complicating cardiopulmonary bypass surgery. Issue 6 (June 1982) - Rigden, S P; Barratt, T M; Dillon, M J; De Leval, M; Stark, J
Abstract : Acute renal failure developed in 24 (5.3%) of 456 children undergoing cardiopulmonary bypass surgery during a 2-year period. It was more common in younger children, in those with complex cardiac lesions, and in those with long overall bypass times. Fourteen (58%) recovered renal function; renal failure was responsible for death in only two. Early vigorous peritoneal dialysis is advocated after cardiopulmonary bypass surgery if there is oliguria (less than or equal to 1.0 ml urine/kg per hour) resistant to volume repletion, dopamine infusion and diuretics, intractable fluid overload, or hyperkalaemia.